Diversity of the Palu Sheep Growth Hormone Gene using the PCR-RFLP Method - Malewa, Amirudin Dg. (AgriSains, 2019)
This study aims to identify the diversity (polymorphism) of the Growth Hormone (GH) gene in Palu sheep as a potential candidate gene that controls the nature of growth. Sheep blood samples from the location of community farms (Palu, Central Sulawesi) which were used as many as 55 animals, were extracted to obtain genomic DNA samples. The detection of diversity in the GH gene was carried out using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP approach with the HaeIII enzyme). The DNA genome was extracted using the phenol-chloroform protocol and amplified with the polymerase chain reaction (PCR) technique, then the product PCR was cut with enzymes. Fragment fragments of the GH-HaeIII locus GH gene (GG-CC) were detected by the silver staining method. A base with a length of 288 bp (PB) from the GH gene was successfully amplified from Palu local sheep. The HaeIII cutting enzyme cuts the PCR product into two different fragments sequentially at 192 and 96 and is expressed as the B allele or BB genotype (homozygous). In conclusion, GH-HaeIII BB locus (homozygous). The restriction results for all PCR products obtained uniform results (no polymorphism) in other words all samples of Palu sheep in a monomorphic state. The DNA pattern in the GH gene is not appropriate for use as a Marker Assisted Selection, because it is monomorphic.